Family-friendly Neighborhood in the Malaysian Perspective: A Review of Literature - Fatimah Hashim, Siti; Norashekin Raja Othman, Raja; Hashim, Habsah; Nasrudin, Na’asah (International Journal of Psychosocial Rehabilitation, 2020)
The increasing number of dual-earner families nowadays to cope with the higher cost and standard of urban living has resulted in several issues concerning communities in the urban neighborhoods. Families need care services for their children and dependents, which range from hiring a full-time maid to sending children to nearby babysitters or faraway care centers. Due to the lack of public facilities and other reasons like seeking quality care, many families opted for private care services. Although the family-friendly cities initiative has been incorporated in the planning profession, there are limited studies discussing the family-friendly neighborhood indicators, especially in Malaysia. Therefore, this paper aims to look at this issue through a review of the literature. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) was adopted for the review of therecent research articles/papers. It was performed in two main journal databases: via (i) Web of Science (WoS) and (ii) Scopus to retrieve high-impact journal articles. The results of the study showed that a number of recommendations were presented for the reference of future scholars in the 31 selected articles after going through the process of identification, screening, eligibility, and inclusion. This study is significant because making neighborhoods family-friendly could improve the quality of life for communities in urban areas.